SWEAR WORDS USED IN FAST AND FURIOUS MOVIE SERIES - Kevin Sean Keefe Louhenapessy (Humaniora Scientia, 2015)
Abstract This research focuses on swear words found in Fast and Furious Movie Series. The aims of this research are to describe the kinds of swear words, the users of swear words and the purposes of uttering swear words. Pragmatic equivalent method is used to describe the kinds of swear words, the users of swear words and the purposes of uttering swear words. In getting the data, the researcher used field research. The data were taken from movie series entitled Fast and Furious; The Fast and The Furious (2001), 2 Fast 2 Furious (2003), The Fast and The Furious Tokyo Drift, Fast and Furious (2009), Fast Five (2011) and Furious 6 (2013). The result of the analysis showed that there were 135 data of swear words based on Hughes’s classifications; they were swear words related to sex (20 items), swear words related to excrement (51 items), swear words related to name of animal (13 items), swear words related to personal background (6 items), swear words related to sexual activity (4 items), swear words related to taboo or religion or oath (38 items) and swear words related to mental illness (3 items). Moreover, the users of swear words are elaborated in the basis of Holmes’s classifications. There were two aspects which influence the users of swear words. The first was the users of swear words based on age. It was divided into swear words which were uttered by youngsters (117 items) and swear words which were uttered by old generation (18 items). The second was the users of swear words based on gender and occupation. It was divided into swear words which were uttered by men (121 items) and swear words which were uttered by women (14 items). Furthermore, the purposes of uttering swear words are categorized based on Eric Partridge’s classifications. They were swear words used to express anger (87 items), swear words used to degrade or put down (10 items), swear words used to express a response of shock (3 items), swear words used to express protest (9 items), swear words used to express intimacy (5 items) and the last classification was swear words used to identify a certain profession (21 items). Key Words: Swear Words, Pragmatics, Taboo